Jenis–Jenis Kayu dan Perhitungan Volume Bahan Pembuatan Kapal Nelayan di Kecamatan Batuda Pantai Kabupaten Gorontalo - Thalib, Rini; Salam, Aziz; Panigoro, Citra (The NIKe Journal, 2025)
This study aims to determine the types of wood used for making fishing boats and how to calculate the volume of wood needed for their manufacture in Olimoo'o Village and Kayubulan Village, Batudaa Pantai District, Gorontalo Regency. This study was conducted from March to September 2024 using a survey method. This study included measuring 50 boat samples, each sample divided into 25 boat samples in Kayubulan Village and 25 samples in Olimoo'o Village. The results showed that the types of wood used by boat craftsmen in making boats in Batudaa Pantai District, especially in the research location, namely Olimoo'o Village and Kayubulan Village, mostly used Nantu wood, namely from 50 sample boats, 17 boats used Nantu wood. Using Tindilo wood (5 boats), Wulu wood (7 boats), Wabo'o wood (6 boats), Binggile wood (5 boats), Talanggilala wood (5 boats), and Teak wood (5 boats). These seven types of wood are highly sought after by fishermen due to their high quality for boat construction. To estimate the wood requirements for boat construction, the plank volume and the length and diameter of the mahera were calculated using the plank volume coefficient (Cp), the mahera length coefficient (Cpm), and the mahera diameter coefficient (Cdm). The calculation results were Cp = 0.0525, Cpm = 0.9231, and Cdm = 0.7447.